Association of vitamin-D deficiency with oxidative stress in newly diagnosed type 2 diabetes - Pradeep Kumar, Bairapogu John; Itaggappa, Maliyannar; Vasudevareddy Thimmaraju, Kamandalagondi (International Journal of Research in Medical Sciences, 2017)
Background: According to a recent World Health Organization (WHO) report, India, with 32 million diabetic individuals, currently has the highest incidence of diabetes worldwide; these numbers are predicted to increase to 80 million by the year 2030. Deficiency of vitamin D has been associated with increased risk of developing Type 2 diabetes mellitus (DM) and cardiovascular diseases. Vitamin D deficiency is highly prevalent in our country. About 70% of adults in both rural and urban areas were found showing manifestations of vitamin D deficiency. Therefore, we designed this study to assess the vitamin D status of the study population by measuring serum 25(OH) D levels, and its association with oxidative stress markers in type 2 diabetes mellitus. Methods: This is a cross sectional study with Group 1 (n=147): Newly diagnosed type 2 diabetics and Group 2 (n=147): Apparently healthy individuals. Blood was collected by venipuncture. 5ml of blood was collected and allowed to clot. Serum was separated and stored in refrigerator to estimate the oxidative stress markers and vitamin D levels. Estimation of vitamin D levels and oxidative stress markers were carried out by commercially available kits. Results: Vitamin D levels are significantly low in newly diagnosed type 2 diabetics when compared to controls (p < 0.000), whereas the FBG levels are significantly high in newly diagnosed type 2 diabetics when compared to controls (p < 0.000). The TAOS levels are significantly low in newly diagnosed type 2 diabetics when compared to controls (p <0.000), whereas the MDA levels are significantly high in newly diagnosed type 2 diabetics when compared to controls (p < 0.000). The oxidative stress marker TAOS (r = 0.71; p < 0.000), was positively correlated and MDA (r = - 0.85; p < 0.000), was negatively with Vitamin D in newly diagnosed type 2 diabetics. Conclusions: From this study, it is concluded that, lower levels of vitamin D is associated with increased oxidative stress. Therapeutic interventions to increase the vitamin D levels and reduce the oxidative stress should be included as a part of treatment inn newly diagnosed type diabetics.